2021
DOI: 10.1002/biof.1791
|View full text |Cite
|
Sign up to set email alerts
|

FERM domain‐containing protein 6 exerts a tumor‐inhibiting role in thyroid cancer by antagonizing oncogenic YAP1

Abstract: The emerging role of FERM domain‐containing protein 6 (FRMD6) in cancer progression has been revealed in several malignancies. However, its relevance on thyroid cancer is not well understood. This work evaluated the possible role and mechanism of FRMD6 in thyroid cancer. We demonstrated that FRMD6 expression was downregulated in thyroid cancer by analyzing the Cancer Genome Atlas data. Remarkable reductions in FRMD6 expression were also confirmed in the clinical specimens and cell lines of thyroid cancer. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…FRMD6 was previously validated as a key upstream regulator of the Hippo signaling pathway that exerted an anti-tumor effect in several human cancers [37]. A recent study demostrated that FRMD6 had a tumor suppressor role by suppressing the activation of carcinogenic YAP1 in thyroid cancer [38]. While Haldrup et al reported that FRMD6 worked as a tumor suppressor gene in prostate cancer [39], they did not explore the upstream regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…FRMD6 was previously validated as a key upstream regulator of the Hippo signaling pathway that exerted an anti-tumor effect in several human cancers [37]. A recent study demostrated that FRMD6 had a tumor suppressor role by suppressing the activation of carcinogenic YAP1 in thyroid cancer [38]. While Haldrup et al reported that FRMD6 worked as a tumor suppressor gene in prostate cancer [39], they did not explore the upstream regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it also indirectly indicates that there is a correlation between FLNC and hypoxia. Cell test and tissue test showed that FERM domain containing 6 (FRMD6) had tumor inhibitory effect in prostate cancer [ 29 ] and thyroid cancer [ 30 ]. In contrast, FRMD6 is a wind risk factor that threatens the prognosis of LUAD in our study.…”
Section: Discussionmentioning
confidence: 99%